2018
DOI: 10.1111/jop.12732
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical diagnosis of mucous membrane pemphigoid

Abstract: Our findings demonstrate that immunohistochemistry for C3d or C4d is a helpful screening procedure for cases of suspected MMP where frozen tissue is not readily available. Negative findings, however, do not exclude a possible diagnosis of MMP and should prompt an additional biopsy for direct immunofluorescence studies. Immunohistochemical detection of IgG or IgA cannot yet be used for the diagnosis of MMP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…The formalin‐fixed, paraffin‐embedded jejunum was used (Canene‐Adams 2013) for the diagnosis of SIgA + cells using and immunohistochemical method according to the procedures of Shimanovich et al . (2018). The average optical density (AOD) of SIgA + cells in the jejunum mucosa was detected using the ImageJ analysis system.…”
Section: Methodsmentioning
confidence: 99%
“…The formalin‐fixed, paraffin‐embedded jejunum was used (Canene‐Adams 2013) for the diagnosis of SIgA + cells using and immunohistochemical method according to the procedures of Shimanovich et al . (2018). The average optical density (AOD) of SIgA + cells in the jejunum mucosa was detected using the ImageJ analysis system.…”
Section: Methodsmentioning
confidence: 99%
“…For DIF, fresh frozen tissue is preferred compared with formalin‐fixed paraffin‐embedded (FFPE) tissue, but DIF on trypsin digestion of formalin‐fixed sections can be an alternative method when fresh frozen tissue is unavailable . In addition, if only FFPE tissues are available, C3d or C4d immunohistochemistry (IHC) has also been considered as a valuable diagnostic tool for bullous pemphigoid (BP) and MMP . IHC for C4d or IgG4 may be diagnostically useful in pemphigus, and C4d IHC can be helpful in the diagnosis of pemphigoid gestationis .…”
Section: Immunological Methodsmentioning
confidence: 99%
“…[4][5][6] In addition, if only FFPE tissues are available, C3d or C4d immunohistochemistry (IHC) has also been considered as a valuable diagnostic tool for bullous pemphigoid (BP) and MMP. [7][8][9][10][11] IHC for C4d or IgG4 may be diagnostically useful in pemphigus, 10,12 and C4d IHC can be helpful in the diagnosis of pemphigoid gestationis. 13 A reliable technique of IHC for IgA and IgG on FFPE tissue needs to be established to obtain higher sensitivity.…”
Section: Direct Immunofluorescencementioning
confidence: 99%
“…13 Two studies found that age and sex did not have an impact on IHC positivity, 11,13 and 3 investigations reported partly contradictory results regarding the impact of positive immunoserology on the sensitivity of IHC (Table 1). 11,13,15 Figure 2 shows the methodological analysis of the included studies based on QUADAS-2, with outcomes resembling bias risk and applicability. Although all studies used an acceptable reference standard (ie, DIF) and low applicability concerns were found consistently across studies, most issues were observed in the risk of bias for patient selection and the index test (ie, IHC).…”
Section: Characteristics and Qualities Of Included Studiesmentioning
confidence: 99%